Probabilistic reachability and control synthesis for stochastic switched systems using the tamed Euler method. (May 2020) - Le Coënt, Adrien; Fribourg, Laurent; Vacher, Jonathan; Wisniewski, Rafael
Abstract: In this paper, we explain how, under the one-sided Lipschitz (OSL) hypothesis, one can find a mean square error bound for a variant of the Euler–Maruyama approximation method for stochastic switched systems. Subsequently, we explain how this bound can be used to control a stochastic switched system in order to make it reach a target zone with guaranteed minimum probability. The method is illustrated on several examples from the literature.